Big Ben - Anderson, Rachel; Ray, Jane (London : Barn Owl Books, 2007)
Ben has profound learning difficulties. Matthew loves his big brother Ben, and loves to have him around. He wants to keep Ben private but finds himself in a difficult situation when he's told to write about his big brother in a school project. To Matthew, school is school and family is private. Even worse is the news that Ben is leaving home.